Rights of vulnerable adults in cross-border situations:: Public policy and adaptation - Adroher Biosca, Salomé (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
In a context conditioned by the likely changes in our private international law on pro- tection of vulnerable adults, I analyze the relevant Resolution of the Provincial Court of Barcelona 330/2022 of October 19 facing the non recognition of measures of incapacitation taken in Morocco, be- cause they are against the new Spanish public policy and the adaptation of the guardianship of adults to equivalent institutions in Spanish law. I will also refer to two other resolutions, that give recognition to the kafalah of vulnerable Moroccan adults in the field of immigration law. I will finish with a reference to the problems of the plurilegislative framework in Spain.